A Longitudinal Cohort Study of Participation in the Boys & Girls Clubs of Winnipeg - Enns, Jennifer; Nickel, Nathan C.; Chateau, Dan; Katz, Alan; Sarkar, Joykrishna; Lambert, Drew; Brownell, Marni (International Journal of Population Data Science, 2022)
Introduction Out-of-school or after-school programs are designed to support healthy behaviours, boost academic achievement and strengthen social skills. The Boys and Girls Clubs of Winnipeg (BGCW) in Manitoba, Canada, have been offering out-of-school programs to children and adolescents in low-income neighbourhoods for more than 40 years. Many BGCW participants face considerable risk of poor health, social and educational outcomes due to challenges they experience at home, in school and in their communities. Objective We examined whether BGCW participation among children and adolescents aged 5-18 is associated with improved school outcomes and lower risk of justice system encounters and adverse health outcomes. Methods We linked de-identified data on BGCW participation for children and adolescents born 1987-2010 to administrative data from the healthcare system, education system, and social services in the Population Research Data Repository, Manitoba Centre for Health Policy. The exposure group (n = 8,990) included children and adolescents who visited BGCW at least once from 2005—2016. The comparison group (n = 69,980) comprised children and adolescents matched on school year and neighbourhood who had never participated in BGCW. Results Participation in BGCW was significantly associated with better scores in grade 3 numeracy and grade 7 student engagement assessments. The risk of justice system encounters among adolescents (aged 12—17) dropped as the frequency of BGCW participation increased, as did justice system encounters among young adults (aged 18—24) who had participated in BGCW as adolescents. The likelihood of teen pregnancy among female adolescents (aged 13—19) and sexually transmitted infections among adolescents (aged 13—19) also declined as the frequency of participation in BGCW increased. Conclusions The findings suggest that participation in BGCW is associated with positive outcomes for children and adolescents in multiple domains and despite socioeconomic and family challenges faced by many in this population.